A performance evaluation approach for MAC protocols of wireless multimedia sensor networks. (2017) - Touil, Hicham; Fakhri, Youssef; Kerroum, Mounir Ait
The performance evaluation and comparison of any proposed medium access control (MAC) protocol with existing MAC protocol is not always an easy step. Seen that, the re-implementation of existing MAC protocols that will be used in comparison takes significant time. As well, there are points that limit the exploitation of the results of an evaluation in future comparison. In this paper, we propose a performance evaluation approach that resolves these points, and offers other advantages. This approach allows assigning MAC protocol after a predefined evaluation steps to a well-predefined performance class. As well, a performance label is generated for the protocol, which contains information on guaranteed quality of service (QoS) that will allow determining strengths and weakness. The generated label for the evaluated protocol will be used in all future MAC protocols comparison, thing that will eliminate time lost in re-implementation and performance evaluation of the protocol.